What do we know about the impact of sexual violence on health and health behaviour of women in Estonia? - Hedda Lippus; Made Laanpere; Kai Part; Inge Ringmets; Helle Karro (BMC, 2020)
Abstract Background Sexual violence against women is a major public health issue and a breach of human rights. Although various consequences of sexual violence on health have been described in a large number of scientific publications, very little is known about this topic in Estonia. The aim of this study was to examine the prevalence of sexual violence and associations between exposure to sexual violence and risky health and sexual behaviours among women in Estonia. Methods A population-based cross-sectional study was carried out in Estonia in 2014. Self-reported data regarding selected indicators of risky health and sexual behaviours were collected from 1670 women, aged 18-44 years, via a self-administered questionnaire. To measure the prevalence of sexual violence, questions from the NorVold Abuse Questionnaire were included. Chi-square and multivariate logistic regression were used to analyse the data. Results Of the respondents, 22.7% (n = 379) reported being exposed to sexual violence during their lifetime, and over half of these women had had these experiences before the age of 18. Statistically significant associations were found between sexual violence and smoking (adjusted odds ratio (AOR) 1.32, 95% CI 1.03-1.70), alcohol consumption (AOR 1.52, 95% CI 1.18-1.95), illicit drug use (AOR 2.21, 95% CI 1.70-2.89), sexual intercourse for money or other material reward (AOR 3.51, 95% CI 1.62-7.61), concurrent sexual relationships (AOR 2.64; 95% CI 1.80-3.86), and being diagnosed with sexually transmitted infections (AOR 1.48, 95% CI 1.09-2.01). Conclusions In Estonia, sexual violence against women is widespread and is associated with several risky health and sexual behaviours. Efforts should be made, both among the general public and professionals, to raise awareness regarding the prevalence and negative impact of sexual violence. Women who have been exposed to sexual violence are in need of professional medical, legal and psychological help free from prejudice to help them recover from such traumatic events.